Effects of Dance Interventions on Aspects of the Participants' Self: A Systematic Review - Schwender, Tina M.; Spengler, Sarah; Oedl, Christina; Mess, Filip (Frontiers in Psychology, 2018)
Background: Theoretical and empirical studies indicate that dance can strengthen the participants’ self. The aim of the systematic review is to give an overview of studies investigating the effects of dance interventions on aspects of the self (e.g. self-concept/-esteem). Research questions are: a) What is the evidence of the reported effects on different aspects of the self in children/adolescents and in adults? b) Which study approaches and designs are used and what characterizes the interventions? c) What are the qualitative facets of the implemented studies and what are issues for future research? Methods: We searched online databases for English and German journal articles with the following main inclusion criteria: (i) Intervention study (qualitative and quantitative approaches) (ii) Investigation of aspects of the self (iii) Dance as intervention content. Two reviewers independently screened studies for eligibility using the PRISMA guidelines and assessed the methodological quality of the included studies. Results: Out of 24 included studies, eleven investigate a sample of children/adolescents and thirteen an adult sample. The review showed that dance interventions can have positive effects on aspects of the participants’ self. The review of studies with qualitative methodologies suggests: children/adolescents benefit in body-related perceptions, self-trust, self-esteem, self-expression and perception of dance-abilities; adults benefit in self-expression, self-efficacy, self-/body-awareness, self-development and self-confidence. Studies with quantitative methodologies report improvement especially for body-related perceptions in both populations. Contradictory results exist concerning self-esteem/-efficacy. The evaluated studies show a heterogeneous nature of populations, intervention contents, timeframes, outcomes, research methods and study quality. Evidence for each of the aspects is still poor due to the small number of studies on each construct, inconsistent findings or methodological shortcomings. Conclusions: This review indicates that dance may be a valuable approach to strengthen aspects of the self. However, as evidence for the different aspects of the self is still poor, further studies with high quality are required (e.g. large samples, active control group). Research considering the complexity and specificity of dance interventions in the design and reporting (e.g. choice of outcomes, presentation of intervention details) seem to be particularly suitable to capture the effects of dance considering its holistic nature.